FINANCIAL LITERACY AND SAVINGS BEHAVIOR FEMALE ENTREPRENEURS IN KIARACONDONG MARKET, BANDUNG CITY - Soukotta, Agnes; Sampe, Ferdinandus; Putri, PA. Andiena Nindya; Cakranegara, Pandu Adi; Yusuf, Muhammad (JURNAL DARMA AGUNG, 2022)
The researcher wants to know if financial literacy can influence saving behavior in Pasar Kiaracondong, Bandung City, by using lifestyle as a moderating variable. The quantitative method was used by the researcher. The data used are of the primary variety. The study's population consisted of 115 female business actors who ran a kiosk in Bandung's Pasar Kiaracondong. Using 53 respondents from the target population in a number of samples. The distribution of online and offline questionnaires was used to collect data using a simple random sampling technique. Path analysis was used in conjunction with the WarpPls 7.0 software. As a result of the test results, financial literacy variables have a positive effect on lifestyle, lifestyle has a positive effect on saving behavior, financial literacy has a positive effect on saving behavior, and lifestyle has the ability to mediate the relationship between financial literacy and saving behavior.